2lnx-ln(2x-1)=

Simple and best practice solution for 2lnx-ln(2x-1)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2lnx-ln(2x-1)= equation:


Simplifying
2lnx + -1ln(2x + -1) = 0

Reorder the terms:
2lnx + -1ln(-1 + 2x) = 0
2lnx + (-1 * -1ln + 2x * -1ln) = 0
2lnx + (1ln + -2lnx) = 0

Reorder the terms:
1ln + 2lnx + -2lnx = 0

Combine like terms: 2lnx + -2lnx = 0
1ln + 0 = 0
1ln = 0

Solving
1ln = 0

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Divide each side by '1'.
ln = 0

Simplifying
ln = 0

The solution to this equation could not be determined.

See similar equations:

| .4x+x^2=.96 | | 8x-8x-5=20 | | 5m=3msquared | | 4x-2=5x+11 | | r^3+24r-160=0 | | .2x+x^2=.99 | | 3t^2+23t-8=o | | 8+10x=26+x | | 0.06x=1730 | | 2X+3X+4=what | | .04+.4x+x^2=1 | | 2(3x+8)=5(x-7) | | q=8p-45 | | 42y+5=71 | | 11x-17=8x+9 | | 12x+3-6x-3=90 | | 9q+54=3q+90 | | 8+2b=10 | | 4j-4=2j+20 | | 3[5-4(4-c)]-5=5[3(5c-4)+2]-26 | | -6+y^2=10 | | x^2+.4x=.96 | | -2x^2+8x-56=0 | | 6x-9=x-4 | | -8+2a=-4 | | Y-25=-3(x-(-7)) | | 2x/3x-5/6 | | 2x^2-8x-56=0 | | 7x-2=-58 | | 5=7n-2 | | 3(x-10)-4=-6x-2 | | x-17=-12 |

Equations solver categories